If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -11 = 3(2y + -1) + -2y Reorder the terms: -11 + 3y = 3(2y + -1) + -2y Reorder the terms: -11 + 3y = 3(-1 + 2y) + -2y -11 + 3y = (-1 * 3 + 2y * 3) + -2y -11 + 3y = (-3 + 6y) + -2y Combine like terms: 6y + -2y = 4y -11 + 3y = -3 + 4y Solving -11 + 3y = -3 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. -11 + 3y + -4y = -3 + 4y + -4y Combine like terms: 3y + -4y = -1y -11 + -1y = -3 + 4y + -4y Combine like terms: 4y + -4y = 0 -11 + -1y = -3 + 0 -11 + -1y = -3 Add '11' to each side of the equation. -11 + 11 + -1y = -3 + 11 Combine like terms: -11 + 11 = 0 0 + -1y = -3 + 11 -1y = -3 + 11 Combine like terms: -3 + 11 = 8 -1y = 8 Divide each side by '-1'. y = -8 Simplifying y = -8
| -2b+5b-7b= | | 63*63= | | (n-2)*4=24 | | -3b+6b= | | 2b-5b+6b= | | 4x=102 | | 6x+49=8x-5 | | -6r-6r= | | -10=1-3p-5 | | -2j+7j= | | -10x+x^2=-25 | | 3(3x+1)=7(x+1) | | 16=-2x-2x | | 3(3x+1)=7(x+3) | | 2x+x+(x+5)=85 | | 29v^2-18v^2=44 | | 3x^3+9x^2+3x-3=0 | | 3y+5x=26 | | 2x+36+20=0 | | n+34=53 | | 3x^2+7=-65 | | 5x^2-2=-82 | | 2x+8-9=63 | | -4+5b-6=-10 | | X*4-61=x*2-13 | | x^3+3x^2y+3xy^2+y^3=-64 | | s(23)=9t-4 | | 3x-2-x^3=0 | | 325-135-89=c | | 8k+3k-4k=56 | | x^3+3x^2y+3xy^2+y^3+64=0 | | v=p*r^2*h |